The Body as Me and Mine: The Case for Property Rights in Attached Body Parts - Singh, Amitpal (McGill Law Journal / Revue de droit de McGill, 2021)
According to a long-standing orthodoxy in the common law, the body is res nullius—nobody’s thing. Recently, this orthodoxy has been challenged. Courts have begun to allow for property in body parts. Yet the law still insists that the body as a whole is res nullius; body parts must be separated from the body to become ownable. I call the prevailing view, according to which separation from the body is morally transformative, the “Separation Thesis.” In this article, I argue that the law should recognize property rights in (some) attached body parts, too. To do this, I develop several candidate rationales for the Separation Thesis, but ultimately expose them as wanting. If separation from the body is not morally transformative, and we can have property rights in detached body parts, then we can have property in our bodies. This view––that less than the entirety of my body is me, and the rest is mine––is also normatively attractive. It readily explains why certain non-biological objects that fulfill bodily functions can become a part of our persons, such as wheelchairs and prosthetics. This view also grounds a right to the parts of our bodies that are not necessary to our existence as separate agents, such as hair. Other accounts struggle to substantiate the biological source’s claim to such body parts because they resist the idea of property in the body. Finally, my account captures both the proprietary and personal wrongs a tortfeasor commits when she excises a body part from another’s body without their consent. All of this implies that we can have personal rights to things outside of the body and property rights to parts of our bodies. This scrambles the intuitive alignment of “person” with “body,” and “property” with “the outside world.”